2019
DOI: 10.2337/dc19-0445
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Eating Behaviors in Adolescents and Emerging Adults With Type 1 Diabetes: A One-Year Prospective Study

Abstract: Disturbed eating behavior (DEB) is prevalent in youth with type 1 diabetes and is accompanied by an increased risk for complications, morbidity, and mortality. Prospective studies on DEB in the challenging transition to adulthood are scarce. This longitudinal study examined DEB over a 1-year period and investigated the directionality of effects linking DEB to diabetes-specific functioning and depressive symptoms in adolescents and emerging adults. RESEARCH DESIGN AND METHODS Three hundred youth (16-28 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 39 publications
(76 reference statements)
0
31
0
1
Order By: Relevance
“…Profiles or subtypes of disordered eating in type 1 diabetes may also differ with respect to their trajectories, with some investigations noting variability in the persistence of symptoms over time . A recent study examining disordered eating at baseline and 1‐year follow‐up in 300 adolescents and young adults with type 1 diabetes observed that 19% of their sample had persistent disordered eating, 8% had worsening disordered eating, and only 7.3% had a reduction in disordered eating . Goebel‐Fabbri et al .…”
Section: What Have the Past 25 Years Of Research Told Us?mentioning
confidence: 99%
See 2 more Smart Citations
“…Profiles or subtypes of disordered eating in type 1 diabetes may also differ with respect to their trajectories, with some investigations noting variability in the persistence of symptoms over time . A recent study examining disordered eating at baseline and 1‐year follow‐up in 300 adolescents and young adults with type 1 diabetes observed that 19% of their sample had persistent disordered eating, 8% had worsening disordered eating, and only 7.3% had a reduction in disordered eating . Goebel‐Fabbri et al .…”
Section: What Have the Past 25 Years Of Research Told Us?mentioning
confidence: 99%
“…Profiles or subtypes of disordered eating in type 1 diabetes may also differ with respect to their trajectories, with some investigations noting variability in the persistence of symptoms over time [5,6,16]. A recent study examining disordered eating at baseline and 1-year follow-up in 300 adolescents and young adults with type 1 diabetes observed that 19% of their sample had persistent disordered eating, 8% had worsening disordered eating, and only 7.3% had a reduction in disordered eating [17]. Goebel-Fabbri et al [18] explored persistence of insulin restriction behaviours in a sample of women with type 1 diabetes (n = 207), finding that those who ceased insulin restriction across the 11-year follow-up period showed less fear of weight gain with insulin, and fewer difficulties with diabetes self-management, relative to those who persisted.…”
Section: What's New?mentioning
confidence: 99%
See 1 more Smart Citation
“…24 The shortage of mental health care resources has previously been documented as a serious concern in the US. 25,26 Combined with the high prevalence of mental health problems such as depression, anxiety, and disturbed eating behaviors in ~10-35% of young adults with type 1 diabetes, 27,28 this shortage constitutes an obstacle for clinical care in this vulnerable age group. There is a need to address this gap in care to make mental health care more accessible and available.…”
Section: Discussionmentioning
confidence: 99%
“…An abundance of research demonstrates that youth are at risk for psychosocial and psychiatric problems, which are associated with worse self‐management and glycemic control 7,8 . However, to date, diabetes research tends to focus mainly on internalizing behavior difficulties such as depression, anxiety, distress, 9 and risk behaviors such as disturbed eating 10 . Despite their link to worse glycemic control in children and adolescents with T1D, 11‐13 externalizing behavior problems remain relatively understudied, and thus potentially under‐assessed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%